Doing Trans-Economic Justice: A Critique of Anti-Discrimination Laws and Inclusive Employment Policies. Issue 2 (22nd August 2020) - Irving, Dan; Hoo, Nathan
Abstract: This article draws on our qualitative study of trans unemployment to introduce considerations of the relationship between trans unemployment and the demands for workers across economic sectors to perform affective labour as integral to industrial service relations. Affective dimensions of labour are often unspoken and unconscious, rendering it challenging for anti-discrimination laws to accommodate. We demonstrate the ways that recent cases grounded on unconscious bias open spaces for further consideration of the ways that trans employment discrimination rooted in demands for affective labour can be dealt with by anti-discrimination law.